2006
DOI: 10.1007/s11284-006-0041-9
|View full text |Cite
|
Sign up to set email alerts
|

Methane oxidation rates in forest soils and their controlling variables: a review and a case study in Korea

Abstract: Methane is one of the strongest of the greenhouse gases, being 30-fold more radiatively active than carbon dioxide on a molar basis. In addition, its atmospheric concentrations have increased by 1% per year since the Industrial Revolution. As such, the dynamics of methane is of great importance for the prediction of global climatic changes caused by increasing concentrations of greenhouse gases in the atmosphere. One of the most important biological sinks for methane is forest soils, where methanotrophic bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 47 publications
7
36
0
1
Order By: Relevance
“…Conversely, for the atmospheric CH 4 the tropical forest soil behaved as a sink in the vegetative season and as a source in the non-vegetative season, respectively. Our data in the temperate forest were in the same range (−2.00∼−7.28 kg CH 4 ha −1 yr −1 ) as found in Asia, Europe and USA (Teepe et al, 2004;Suwanwaree and Robertson, 2005;Jang et al, 2006;Morishita et al, 2007), and were less than the global average of −5.60 kg CH 4 ha −1 yr −1 (Jang et al, 2006). Additionally, CH 4 fluxes in the tropical and subtropical forest soils were comparable with those of other tropical forest soils (−2.10∼−6.59 kg CH 4 ha −1 yr −1 , Verchot et al, 2000;Davidson et al, 2000;Silver et al, 2005;Ishizuka et al, 2005;Werner et al, 2006, Werner et al, 2007.…”
Section: Comparisons With Other Studiessupporting
confidence: 80%
“…Conversely, for the atmospheric CH 4 the tropical forest soil behaved as a sink in the vegetative season and as a source in the non-vegetative season, respectively. Our data in the temperate forest were in the same range (−2.00∼−7.28 kg CH 4 ha −1 yr −1 ) as found in Asia, Europe and USA (Teepe et al, 2004;Suwanwaree and Robertson, 2005;Jang et al, 2006;Morishita et al, 2007), and were less than the global average of −5.60 kg CH 4 ha −1 yr −1 (Jang et al, 2006). Additionally, CH 4 fluxes in the tropical and subtropical forest soils were comparable with those of other tropical forest soils (−2.10∼−6.59 kg CH 4 ha −1 yr −1 , Verchot et al, 2000;Davidson et al, 2000;Silver et al, 2005;Ishizuka et al, 2005;Werner et al, 2006, Werner et al, 2007.…”
Section: Comparisons With Other Studiessupporting
confidence: 80%
“…According to this Table 4 Methane oxidation rates in forest reported for different climatic zones (modification from Smith et al 2000) Methane oxidation rate (kg CH 4 ha -1 y -1 ) The sources of data are listed below Temperate forest/woodland in Asia: Morishita et al 2007, Jang et al 2006, Du et al 2004, Dong et al 2003, Kagotani et al 1999, Morishita and Hatano 1999 Temperate forest/woodland in Europe: Fiedler et al 2005, Castaldi and Fierro 2005, Merino et al 2004, Bradford et al 2001, Steinkamp et al 2001, Brumme and Borken 1999, Dong et al 1998, Borken and Brumme 1997, Klemedtsson and Klemedtsson 1997, MacDonald et al 1997, Ambus and Christensen 1995, Dörr et al 1993, Koschorreck and Conrad 1993 Temperate forest/woodland in North America: Borken et al 2006, Groffman et al 2006, McLain and Martens 2006, Suwanwaree and Robertson 2005, Teepe et al 2004, Phillips et al 2001, Bowden et al 2000, Rustad and Fernandez 1998, Hudgens and Yavitt 1997, Castro et al 1993, Goldman et al 1995, Lessard et al 1994, Adamsen and King 1993, Yavitt et al 1993, Crill 1991, Steudler et al 1989 Temperate forest/woodland in Oceania: Tate et al 2006…”
Section: Comparison Of Ch 4 Uptake Rate With Other Reportsmentioning
confidence: 99%
“…These figures compare well with the estimate of Dutaur and Verchot (2007) of a reduction by 17% to 40% of the CH 4 sink strength. Due to the strong impact of N addition on CH 4 uptake, intensive research in the laboratory and the field has addressed this topic (Goldman et al 1995;Bradford et al 2001bBradford et al , 2001aJang et al 2006;Borken and Brumme 2009;Bodelier 2011b). In various field studies (King and Schnell 1994a;Dobbie and Smith 1996;Steinkamp et al 2001) and laboratory experiments (Adamsen and King 1993;Bender and Conrad 1994;Priemé and Christensen 1997;MacDonald et al 1997), evidence was found for an inhibiting effect of ammonium (NH 4 + ) fertilisation on CH 4 oxidation in forest soils.…”
Section: Introductionmentioning
confidence: 99%